A quantum optical study of thresholdless lasing features in high-β nitride nanobeam cavities - Stefan T. Jagsch (Nature Portfolio, 2018)
Here the authors present temperature dependent studies of GaN nanobeam lasers grown on a silicon substrate and demonstrate high-βlasing at room temperature. Comprehensive optical and quantum-optical characterization, complemented by microscopic modeling, of the nanolasers allow identification of lasing behavior.